2022
DOI: 10.3390/foods11213313
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pulsed Electric Fields and pH on Enzyme Inactivation and Bioactivities of Peptic Hydrolysates Produced from Bovine and Porcine Hemoglobin

Abstract: The production of bioactive peptides from hemoglobin via peptic hydrolysis is a promising alternative to valorizing slaughterhouse blood proteins. Nevertheless, it has some limitations such as low yield, high cost of enzymes, and the use of chemical reagents. The latter is aggravated by the pH increase to inactivate the enzyme, which can affect the bioactivity of the peptides. Thus, this study aimed to evaluate the effect of pulsed electric fields (PEF) on the pepsin inactivation and biological activities (ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…PEF processing involves applying short pulses (microseconds to milliseconds) of high voltage electric field to materials placed between two electrodes, and the applied electric field strength can vary from 10 to 80 kV/cm. , Although it requires large specific energy to inactivate enzymes compared to microbial inactivation, PEF has been reported to be an effective strategy to significantly inactivate the most undesirable enzymes in the preservation of food products. This approach allows changing the physicochemical and biochemical properties of proteins by affecting the three-dimensional structural elements of proteins due to the interaction between the electric field and their dipole moments, as well as the ionization of the radical groups of carboxylic groups (−COO – ), amino groups (−NH 3 + ), and electrically charged residues (lysine, arginine, histidine, aspartic acid, and glutamic acid). , However, available evidence has reported that low-intensity exposure to PEF can also induce the activities of useful enzymes. This method is in trouble with two major disadvantages in terms of use.…”
Section: Different Triggering Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PEF processing involves applying short pulses (microseconds to milliseconds) of high voltage electric field to materials placed between two electrodes, and the applied electric field strength can vary from 10 to 80 kV/cm. , Although it requires large specific energy to inactivate enzymes compared to microbial inactivation, PEF has been reported to be an effective strategy to significantly inactivate the most undesirable enzymes in the preservation of food products. This approach allows changing the physicochemical and biochemical properties of proteins by affecting the three-dimensional structural elements of proteins due to the interaction between the electric field and their dipole moments, as well as the ionization of the radical groups of carboxylic groups (−COO – ), amino groups (−NH 3 + ), and electrically charged residues (lysine, arginine, histidine, aspartic acid, and glutamic acid). , However, available evidence has reported that low-intensity exposure to PEF can also induce the activities of useful enzymes. This method is in trouble with two major disadvantages in terms of use.…”
Section: Different Triggering Methodsmentioning
confidence: 99%
“…This approach allows changing the physicochemical and biochemical properties of proteins by affecting the three-dimensional structural elements of proteins due to the interaction between the electric field and their dipole moments, as well as the ionization of the radical groups of carboxylic groups (−COO − ), amino groups (−NH 3 + ), and electrically charged residues (lysine, arginine, histidine, aspartic acid, and glutamic acid). 102,104 However, available evidence has reported that low-intensity exposure to PEF can also induce the activities of useful enzymes. This method is in trouble with two major disadvantages in terms of use.…”
Section: Effect Of Magnetic Fieldmentioning
confidence: 99%